technological development and itsimpact on tourism growth in the Kurdistan region of Iraq in 2023 - Rana Muzahem Jihad (Journal of College of Education, 2024)
The research addressed the impact of technological development and its impact on tourism growth in the Kurdistan Region of Iraq (Technological development represents an important factor in promoting tourism growth in the Kurdistan Region of Iraq on several aspects). Marketing tourist destinations. The use of social media and other digital platforms can enhance the promotion of tourist attractions in the region. Online photos and videos can attract the attention of potential travelers and encourage them to visit the area. Improve tourism services. Technology makes it easier to improve hospitality and accommodation services, including online reservations and providing accurate information about hotels, restaurants, and tourist activities. This enhances the comfort and satisfaction of visitors and makes their experience better promoting local culture. This helps in enhancing awareness of the region and attracting cultural travelers. Natural and human factors have played an important role in attracting tourists, and technology has an impact on types of tourism, including cave, therapeutic, environmental, recreational, mountain, and sports tourism. The percentage of arrivals varies in Erbil, Dohuk, and Sulaymaniyah